On a class of $(a,k)$-regularized $C$-resolvent families - Marko Kostic (Electronic Journal of Qualitative Theory of Differential Equations, 2012)
In this paper, we investigate the basic structural properties of (analytic) q-exponentially equicontinuous $(a,k)$-regularized $C$-resolvent families in sequentially complete locally convex spaces. We provide some applications in fluid dynamics, linear thermoviscoelasticity, and illustrate obtained theoretical results by several other examples.